The Toyota way to lean leadership achieving and sustaining excellence through leadership development - Liker, Jeffrey K. (McGraw-Hill, 2012)
From the bestselling author of The Toyota Way, the missing link to sustainable lean success--a four-step leadership model that aligns company culture with lean processes